Mixed Race Stereotypes in South African and American Literature - Mafe, D. author. aut Link
XII, 195 p. 3 illus.
Keywords: Mixed Race Stereotypes in South African and American Literature examines the popular literary stereotype, the tragic mulatto, from a transnational perspective. Mafe considers the ways in which specific South African and American writers have used this controversial literary character to challenge the logic of racial categorization.